Evaluating the content of science curriculum in the first year of Intermediate schools in Saudi Arabia - Al Shehri, Rawan Zafer Ali (Journal of Educational and Psychological Sciences, 2018)
The aim of the research is to learn about the international standards of science education and its presence in science curricula in the first year of Intermediate schools in Saudi Arabia. To answer the research questions, the researcher sets out a list of science education standards in the light of four international standards for science education (concepts and processes, science as demand, science technology, and social science perspective). This list consists of (23) criteria. And (70) indicators. And The research sample consists of scientific books for the first year of the first and second term.The results of research showed that the International standards are found with the order: concepts and processes then science as a science and then science and technology then a personal social science perspective. There is a failure in science curricula that cause low acquisition of science and operations, science as first-year science, technology and technology skills for Intermediate students. and There is a failure of inclusion of scientific and technological criteria in the content of textbooks. In the light of the results, a number of recommendations and suggestions were presented to develop science curricula in the light of the international standards of science education. The most important of these is the need for developers of the science curriculum to pay attention to the international standards of science education, especially the field of science and technology and science from a personal and social perspective. The interest in the revision of the content and activities of the science curriculum in the intermediate phase of overfill, as the amount of information is a prominent feature in his textbooks its stage, which hinders development in the light of scientific education standards.
Keywords: calendar; Science curriculum; The first average; global standards; Science education